2020
DOI: 10.3390/v12090990
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of Egyptian Foot-and-Mouth Disease Virus Field and Vaccine Strains: Intertypic Recombination and Evidence for Accidental Release of Virulent Virus

Abstract: In spite of annual mass vaccination programs with polyvalent inactivated vaccines, the incidence and economic impact of foot-and-mouth disease (FMD) in Egypt is high. Viruses of the A, O and SAT 2 serotypes are endemic and repeated incursions of new lineages from other countries lead to an unstable situation that makes the selection of appropriate vaccine antigens very difficult. In this study, whole genome sequencing of a 2016 serotype A isolate from Egypt revealed a recombination event with an African seroty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Strain (O/EGY/10/2011) is commonly included in the current local vaccines. Sobhi et al [9] observed two different strains of serotype O, one related to PanAsia-2 in Upper Egypt and the Delta (i.e., most of Egypt) and the other, was probably less immunodominant and related to the East African strains in Sharkia province This is not in line with the conclusions of Abdel Rahman et al [1], who reported that the vaccinal strain of serotype O has shown variable sequence alignment and phylogenecity profiles, being generally comparable to other O/ME-SA strains, while the leader protein-coding zone (five prime untranslated region) was more or less similar to those of some historical EURO-SA vaccine strains, including O1/Campos/BRA/58 and O1/BFS1860/UKG/67. The authors also report that the virus in the inactivated vaccine (of lineage O/ME-SA, box A) was very distant from the lineage O/EA-3 strains (box B).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Strain (O/EGY/10/2011) is commonly included in the current local vaccines. Sobhi et al [9] observed two different strains of serotype O, one related to PanAsia-2 in Upper Egypt and the Delta (i.e., most of Egypt) and the other, was probably less immunodominant and related to the East African strains in Sharkia province This is not in line with the conclusions of Abdel Rahman et al [1], who reported that the vaccinal strain of serotype O has shown variable sequence alignment and phylogenecity profiles, being generally comparable to other O/ME-SA strains, while the leader protein-coding zone (five prime untranslated region) was more or less similar to those of some historical EURO-SA vaccine strains, including O1/Campos/BRA/58 and O1/BFS1860/UKG/67. The authors also report that the virus in the inactivated vaccine (of lineage O/ME-SA, box A) was very distant from the lineage O/EA-3 strains (box B).…”
Section: Introductionmentioning
confidence: 86%
“…The article by Abdel Rahman et al [1] reported that 62 clinical samples (blood, serum, white blood cells and swabs from the nose, mouth and saliva) were collected from two cattle and 2 buffaloes in 2016. Only saliva samples from the 4 animals were positive for FMDV serotype A by PCR, but the virus was detected in cell cultures from 3 samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleic acids were extracted from 100 µL of each sample with the NucleoMag VET kit (Macherey-Nagel, Düren, Germany) on a KingFisher Flex Magnetic Particle Processor (Thermo Fisher Scientific, Waltham, MA, USA) following the manufacturers’ instructions. The extracted nucleic acids were tested for AlHV-1 [ 19 ] and OvHV-2 [ 20 ] DNA by real-time PCR using the PerfeCTa qPCR ToughMix (Quantabio, Beverly, MA, USA) in a CFX96 thermocycler (Bio-Rad, Hercules, CA, USA) as well as for FMD virus [ 21 ], BVDV [ 22 ], and BoHV-1 [ 23 ] as previously described. A lymphoid tissue preparation from an Italian case of sheep-associated bovine MCF from 2007 (record no.…”
Section: Methodsmentioning
confidence: 99%